SHALLOW SLAB DETACHMENT AS A TRANSIENT SOURCE OF HEAT AT MIDLITHOSPHERIC DEPTHS - van de Zedde D.M.A.; Wortel M.J.R. (My University, 2001)
Slab detachment (or breakoff) has been proposed as a cause of temperature-related processes associated with subduction, such as postcollisional magmatism, mineralization, and metamorphism. In this study, we quantitatively investigate the breakoff process and the subsequent thermal evolution of a plate boundary region involving continental collision after a prolonged period of oceanic lithosphere subduction. Our two-dimensional time-dependent thermomechanical modeling shows that the dense, oceanic part of the slab can become detached at depths as shallow as 35 km. The detached part of the slab sinks into the mantle, creating a gap in the lithospheric system which is filled with upwelling hot asthenosphere. The resulting temperature increase in the overlying material can be more than 500°C. It allows for partial melting of the asthenosphere and the overriding metasomatized lithosphere for a timespan of a few millions of years. Crustal anatexis and related magmatism and mineralization can proceed over a considerably longer period. The quantification of the conditions required for shallow slab detachment will contribute to warranted assessments concerning the role of slab detachment (relative to other proposed heat sources, such as tectonically accreted radioactive material) in the geodynamical evolution of former convergent plate boundaries.